BUILDING THE FOUNDATION OF AN ETHICAL AND MORAL-BASED LEARNING CULTURE IN GRADE VI STUDENTS IN MI DARUL MUHTADIN, TALANGO DISTRICT, SUMENEP REGENCY, EAST JAVA - Lillah, Fadl; Kawakip, Akhmad Nurul; Susilawati, Samsul (Yayasan Adra Karima Hubbi, 2025)
The development of an ethical and moral–based learning culture is a core mission of Islamic elementary education, particularly at the upper-grade level where students experience significant cognitive and character formation. In many madrasah ibtidaiyah, learning practices still prioritize academic achievement, while ethical values and moral behavior are often taught implicitly and inconsistently. This condition necessitates a more systematic approach to embedding ethical and moral principles within everyday learning culture. This study aims to analyze the process of building an ethical and moral–based learning culture among Grade VI students at MI Darul Muhtadin, Talango District, Sumenep Regency, East Java, and to examine its influence on students’ learning attitudes and social behavior. This research employed a qualitative case study design. Data were collected through classroom observations, semi-structured interviews with teachers, school leaders, and students, as well as analysis of school documents. The data were analyzed thematically to identify strategies, patterns, and outcomes of moral and ethical habituation. The findings reveal that ethical and moral values were effectively fostered through teacher role modeling, routine religious and character-building activities, integrative instructional practices, and consistent enforcement of school norms. These efforts resulted in observable improvements in students’ discipline, respectfulness, responsibility, and cooperative learning behavior. Establishing an ethical and moral–based learning culture requires intentional integration of values into pedagogy, school routines, and institutional policies to support sustainable character development among students.